Kontribusi Implementasi Manajemen Berbasis Nilai-Nilai Kearifan Lokal Tri Hita Karana, Kepemimpinan, Budaya Organisasional dan Kepuasan Kerja Terhadap Kinerja Pegawai di Perumda Bhukti Praja Sewakadarma di Kota Denpasar - Astriani, Ni Putu Dian; Agung, Anak Agung Gede; Sulindawati, Ni Luh Gede Erni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to assess several aspects regarding the performance of State High School teachers in Denpasar City, namely: 1) the level of determination of transformational leadership on teachers' performance, 2) the level of determination of work ethic on teachers' performance, 3) the level of determination of organizational commitment on teachers' performance, 4) the level of determination of work motivation on teachers' performance, and 5) the combined determination of transformational leadership, work ethic, organizational commitment, and work motivation on the performance of State High School teachers in Denpasar City. The study employed an "ex-post facto" approach with a large sample of 233 participants. The findings revealed significant insights: Firstly, there was a significant determination between transformational leadership and teachers' performance, with a correlation coefficient of 0.433 and an effective contribution of 9.01%. Secondly, there was a significant determination between work ethic and teachers' performance, with a correlation coefficient of 0.314 and an effective contribution of 4.71%. Thirdly, there was a significant determination between organizational commitment and teachers' performance, with a correlation coefficient of 0.255 and an effective contribution of 0.38%. Fourthly, there was a significant determination between work motivation and teachers' performance, with a correlation coefficient of 0.513 and an effective contribution of 19.01%. Finally, collectively, there was a significant determination between transformational leadership, work ethic, organizational commitment, and work motivation on teachers' performance, with a double correlation coefficient of 0.575 and a determination of 33.1% on the performance of State High School teachers in Denpasar City.